Labour market reforms, institutions, and the quality of employment : should we all follow German Hartz model in reforming labour markets? - Mähönen, Erno (2015)
Underemployment and aging population are major threats for several European economies. This study asks, whether partial labour market reforms, similar to German Hartz reforms, were good choices for other European countries, especially in terms of the quality of employment. Labour market liberalisation effects are assessed from macro-perspective on 25 OECD countries with fixed-effects panel data analysis. The effects for full-time, part-time, temporary, and low-wage employment are analysed separately for both genders, and also on young adults. The results find out strongly a gendered nature of labour market deregulation effects, which give support for dual labour market theory. There appears to be a two-way substitution effect caused by labour market deregulation: a shift from male to female employment and from full-time to part-time employment. Young adults seem to gain less from the reforms than older cohorts while gender differences are also lower for the youth. While liberalisation of temporary contracts seems to moderately increase overall employment, there is a risk of increased precarisation. Moreover, the results suggest that wage-setting institutions shape employment structure much more deeply than employment protection legislation.